Evaluating tumor response with FDG PET: updates on PERCIST, comparison with EORTC criteria and clues to future developments - Pinker, Katja (Eur J Nucl Med Mol Imaging, 2017)
Eighteen years ago, the EORTC PET criteria standardized for the first-time response assessment by FDG PET. Response assessment by FDG PET has been further developed and refined by PERCIST (PET response criteria in solid tumors). This review describes the data underlying these two systems for assessing tumor response on FDG PET/CT. It also summarizes recent clinical studies that have compared EORTC criteria and PERCIST with each other as well as with the anatomically based “response criteria in solid tumors” (RECIST). These studies have shown that response assessment by EORTC criteria and PERCIST leads to very similar response classifications. In contrast, there are significant differences between response assessment by PERCIST and RECIST. Preliminary data also suggest that response assessment by PERCIST is better correlated with patient outcome and may be a better predictor for the effectiveness of new anti-cancer therapies than RECIST. If correct, this could have a significant impact on oncologic drug development. However, confirmation of the better predictive value of response assessment by PERCIST by data from randomized trials is still lacking.